ANALISIS PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI KECAMATAN COLOMADU KABUPATEN KARANGANYAR - Praptiestrini, - (Universitas Slamet Riyadi, 2016)
The purpose of this study were to analyze: 1) )the influence of work environment to job satisfaction, 2)the influence of leadership to job satisfaction. This research is survey research. Primary data obtained from questionnaires to 40 respondents and performed analyzes with SPSS, with the results all questionnaires are valid and reliable. The data analysis using with multiple linear regression analysis, t-test, F-test, and R total. The result showed that: 1) work environment significantly to job satisfaction 2) leadership influence significantly to job satisfaction.Keywords: work environment, leadership, and job satisfaction